Emotional labor, employee workplace behaviors, organizational support and emotional intelligence : An empirical investigation on foreign service workers in Sabah and Labuan - Tan, Siew Luen (2013)
This study aimed to identify factors that determine entry-level job expectations of graduating students from Malaysia and Australia as entry-level job seekers. The factors were pay expectation, job security, company reputation, working condition, type of work, location of workplace, flextime, career advancement opportunity, and training opportunity. The present study also attempted to explore whether graduating student's entry-level job expectations are different across nationality (i.e., Malaysian vs. Australian) and gender (i.e., Male vs. Female). In addition, the current study examined how Malaysian and Australian graduating students rank these entry-level job expectations in terms of importance to them as entry-level job seekers. Using area sampling technique, questionnaires were distributed to 400 respondents in Malaysia and Australia. A total of 310 questionnaires were collected but only 268 questionnaires were found usable. The data were analyzed using several statistical analyses including factor analysis, reliability analysis, and test of differences. The results revealed that Malaysian and Australian graduating students were significantly different with regard to three job characteristics namely company reputation, working condition, and career advancement and training opportunity. Furthermore, the study found that male and female graduating students in Malaysia only or both countries were significantly different in terms of working condition. Interestingly, the study findings confirmed that pay expectation was perceived to be the most important factor by the graduating students, regardless of where they are from. Whereas type of work was cited as the least important job characteristic in selecting their entry-level jobs. The findings of this study can be beneficial for graduating students as they enter the job market, as well as for human resources managers in attracting and retaining potential employees from the pool of fresh graduates.